Pemeliharaan Kesehatan Lansia Aktif dan Sehat melalui “Foot Exercise” sebagai Pencegahan Komplikasi Diabetes Mellitus: Active and Healthy Elderly Health Maintenance through “Foot Exercise” as Prevention of Diabetes Mellitus Complications - Safariyah, Erna; Danismaya, Irawan; Hamzah, Amir; Alamsah, Mustopa Saepul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Diabetes mellitus is one of the chronic diseases with an increasing incidence every year. The increasing number of people with Diabetes Mellitus can be influenced by several factors, such as the economy, lack of knowledge and unhealthy lifestyle, age, and also overweight. Cases of diabetes mellitus in Sukabumi City have increased, including in Lembursitu (9.8%). The solution offered is to maintain health through health education and